The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1017/s0047404520000330
|View full text |Cite
|
Sign up to set email alerts
|

‘Converse racialization’ and ‘un/marking’ language: The making of a bilingual university in a neoliberal world

Abstract: The discourse on the opening of a bilingual university along the Texas-Mexico border leads us to propose a theory of ‘converse racialization’ through which the local Spanish is being progressively ‘unmarked’ and disassociated from the language practice of Mexican Americans. Converse racialization, as the equal and opposite co-constituting underside of racialization, shifts the directionality of semiotic indexes away from a particular ‘race’ or ‘ethnicity’ (including whiteness) and produces an apparent state of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Our analysis certainly has shown that university admission requirements continue to racialize English as a White language of the Anglophone center. However, simultaneously, and echoing Mena & García's (2021) findings in another context of neoliberal higher education, a process of converse racialization is at work where the White-English complex is being unmarked. This happens when inherent ELP is not only ascribed to inner circle applicants but also to applicants from a long list of outer circle countries.…”
Section: O N C L U S I O Nmentioning
confidence: 75%
“…Our analysis certainly has shown that university admission requirements continue to racialize English as a White language of the Anglophone center. However, simultaneously, and echoing Mena & García's (2021) findings in another context of neoliberal higher education, a process of converse racialization is at work where the White-English complex is being unmarked. This happens when inherent ELP is not only ascribed to inner circle applicants but also to applicants from a long list of outer circle countries.…”
Section: O N C L U S I O Nmentioning
confidence: 75%
“…More suggestively, she saw this shift as an opportunity to raise her subaltern voice as a teacher and reveal oppressing experiences she lived that would shape her own view of culture and consequently her views of teaching, learning, and living. Considering Mena and García (2020), this shift that the student developed in her project clearly describes deracialisation and, we add, decolonisation of the language teaching environment, where counter-stories (a strategy that has also been adopted by decolonial theory) support alternative views of reality and dismantle big narrative towards a stereotyped English teaching milieu.…”
Section: íKalamentioning
confidence: 98%
“…In this new perspective, she found, as Mena and García (2020) and Flores and Rosa (2015), that she would value the students' experiences and voice rather than just focus on her only view being an outsider. More suggestively, she saw this shift as an opportunity to raise her subaltern voice as a teacher and reveal oppressing experiences she lived that would shape her own view of culture and consequently her views of teaching, learning, and living.…”
Section: íKalamentioning
confidence: 99%
See 1 more Smart Citation
“…Standard American English (SAE) at U.S. colleges often creates a learning obstacle for students who speak different languages (Lawton 2013; Snell 2013). Additionally, standard language ideologies frequently act as gatekeeping devices that require students' linguistic obedience in exchange for opportunities to be represented in universities (Mena and Garcia 2021; Cushing 2020; Shohamy 2006). As Jonathan Rosa and Nelson Flores (2020, 103) argue, “Efforts to facilitate racialized populations' mastery of supposed ‘codes of power’ are not empowering … but rather a mechanism for producing governable subjects that support the raciolinguistic status quo.” 1 In the present contribution we argue that strict adherence to SAE keeps people from learning new ways of being and innovating fresh practices and perspectives.…”
mentioning
confidence: 99%